Сold treatment and alloplasty for a resection defect of an extensive giant cell tumour in the proximal tibia (description of a case) - Demichev, Nikolay; Kroshkina, Valeriya (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2010)
The WHO Histological Classification of Tumours considers the giant cell tumor of bone (GCTB) (osteoclastoma) as potentially malignant. Currently, the need for surgical treatment of this pathology is beyond doubt. The efficacy of surgical intervention in such patients significantly reduces as result of a high tendency of GCTB to recur. The use of adjuvant cryotherapy in treatment of GCTB made it possible to reduce the number of local recurrences down to 3.5 %. Thus, the cryosurgical technique of treatment with alloplasty of the resection defect is still an effective way of treatment, which makes it possible to avoid mutilating surgery.